Re-branding UMKM Kelurahan Kedundung Mojokerto Melalui Logo Baru yang Unik dan Menarik: Re-branding UMKM Kelurahan Kedundung Mojokerto Melalui Logo Baru yang Unik dan Menarik - Ifwarisan Defri; Erwan Adi Saputro; Arif Al Furkhom; Bella Wanda Anastasia (Abdi-mesin: Jurnal Pengabdian Masyarakat Teknik Mesin, 2022)
The Covid-19 pandemic has brought many people who have businesses out of their businesses. Therefore, the community is required to be able to adapt to the conditions that occured, by making efforts to renew or rebrand their business to be better and be able to survive in the market. In addition, rebranding can generate brand awareness and product brand image. The general purpose of this rebranding program or logo creation is to make UMKM have their own characteristics and become a differentiator between fellow UMKM. As well as in terms of promotion, consumers can also easily recognize a product. The existence of a logo also makes a business product attractive to attract more customers. By using field survey methods and online surveys through WhatsApp media as well as discussions with UMKM owners, it was found that the existence of a new logo made consumers interested in buying and products that were rebranded became more easily known by consumers because of uniqueness and attractiveness of the logo. Keywords: logo, rebranding, UMKM